Factors Influencing the Intention to Use Mobile Payment In Indonesia - Christina Christina; Hepy H Ariyanto; Pulung Peranginangin (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
Mobile payment has become the trend in the e-banking and e-commerce industry in Indonesia in consort with the development of Information technology, which allows financial services to create faster, more efficient, and more convenient services for customers in the payment system. Despite the surge of mobile payment used in Indonesia following the impact of the pandemic of Covid-19, there are still many challenges and inconclusiveness regarding the research on the adoption of mobile payment services. This study’s purpose is to examine the Intention to use Mobile payment in Indonesia. A total of 402 Indonesian respondents are collected using online questionnaires. The proposed model was empirically examined using a quantitative method with PLS-SEM. The empirical results of this study shows that Social Influence, Perceived Trust, and Facilitating Condition were found to be significantly influencing the Attitude towards Intention of using mobile payment. Meanwhile Perceived Ease of use and Perceived Risk are found to be insignificantly influenced by the intention to use mobile payment.